Effects of waste paper sludge ash on compressive strength of concrete cubes / Marzuki A.Rahman ...[et al.] - A.Rahman, Marzuki; Hisham, Mohd Syahrul; Jaafar, Mohd Risham; Ruslan, Ahmad; Mohd Saman, Hamidah (2006)
Waste paper sludge incinerator ash (WPSIA) was investigated for its potential use as a replacement for cement in concrete. The physical and chemical properties of raw materials were determined. The water cement ratio was fixed at 0.55 while WPSIA was used at 5%, 10%, 15%, 20%, 25% and 30% replacement by weight of cement. The grade design of proportions was 30 N/mm2. Slump and compressive strengths were performed on all specimens. Results indicate the WPSA caused a reduction in slump values when it was used as a cement replacement. The replacement of WPSIA up 30% exhibited, generally similar to control mix (0% WPSIA) after 28 days of curing. The maximum compressive strength of 44.1 N/mm2 was achieved using 15% of WPSIA after 60 days of curing. The experimental results presented in this study suggest the potential of WPSIA as a cement replacement. With strength contributing and nontoxic characteristic, the use of WPSIA as a cement replacement may be technically and environmentally feasible.